Antimicrobial Activity of Metabolites Secreted by the Endophytic Bacterium Frateuria defendens - Alaa Naama-Amar; Shani Gitman; Nofar Shoshana; Ofir Bahar; Vered Naor; Einat Zchori-Fein; Lilach Iasur-Kruh (Plants, 2020)
Candidatus Phytoplasma, the causative agent of yellows disease, inflicts substantial damage on several hundred plant species including perennials and annual plants. The endophytic bacterium Frateuria defendens reduces the symptoms of yellows disease in a number of agricultural crops. One possible mode of action is that the bacterium secretes antimicrobial metabolites. To test this hypothesis, the substances secreted by the endophyte during 10 days of growth in an artificial medium were identified by GC-MS (gas chromatography−mass spectrometry). Synthetic analogues to these substances were then used on periwinkle, a nurse culture plant infected by phytoplasma. Phytoplasma quantities were evaluated by quantitative PCR, and disease symptoms were monitored and recorded. It was found that specific compounds identified by the biochemical analysis caused a significant reduction in both the titer of phytoplasma and the disease symptoms in periwinkle when compared to untreated infected plants. Further research is required to examine the potential of these compounds as an effective treatment against yellows disease.